Risk factors for failure in the newborn hearing screen test in very preterm twins - So Young Kim; Byung Yoon Choi; Eun Young Jung; Hyunsoo Park; Ha-Na Yoo; Kyo Hoon Park (Pediatrics and Neonatology)
Background: We aimed to identify prenatal and postnatal risk factors associated with abnormal newborn hearing screen (NHS) results and subsequently confirmed sensorineural hearing loss (SNHL) in preterm twin neonates. Methods: Electronic medical records of 159 twin neonates who were born alive after ≤32 weeks were retrospectively reviewed for hearing loss in both ears. Histopathologic examination of the placenta was performed and clinical data, including method of conception and factors specific to twins, were retrieved from a computerized perinatal database. The main outcome measure was failure to pass the NHS test. The generalized estimation equations model was used for twins. Results: Thirty-two neonates (20.1%) had a “refer” result, and, on the confirmation test, permanent SNHL was identified in 4.4% (7/159) of all neonates. Neonates who had a “refer” result on the NHS test were more likely to be of lower birth weight, more likely to have been conceived with the use of in vitro fertilization (IVF), and more likely to have higher rates of intraventricular hemorrhage (IVH) and bronchopulmonary dysplasia. However, monochorionic placentation, death of the co-twin, or being born first was not associated with a “refer” result on the NHS test. Multivariable logistic regression revealed that conception after IVF and the presence of IVH were the only variables to be statistically significantly associated with “refer” on the NHS test. No parameters studied were found to be significantly different between the SNHL and no SNHL groups, probably because of the relatively small number of cases of SNHL. Conclusion: In preterm twin newborns, IVF and the presence of IVH were independently associated with an increased risk of abnormal NHS results, whereas the factors specific to twins were not associated with abnormal NHS results. Key Words: in vitro fertilization, newborn hearing screen test, preterm, refer, twins